Bluecrowne : a Greenglass House story - Milford, Kate (Milford, Kate. Greenglass house., 2018)
Lucy Bluecrowne is beginning a new life ashore with her stepmother and half brother, though she's certain the only place she'll ever belong is with her father on a ship of war as part of the crew. She doesn't care that living in a house is safer and the proper place for a twelve-year-old girl; its boring. But then two nefarious strangers identify her little brother as the pyrotechnical prodigy they need to enact an evil plan, and it will take all Lucy's fighting instincts to keep her family together.